Early Elevation in Interleukin-6 is Associated with Reduced Growth in Extremely Low Birth Weight Infants - Denson, Lee A. (Am J Perinatol, 2016)
OBJECTIVE: To determine whether reduced growth velocity (GV) in extremely low birth weight (ELBW) infants is preceded by elevated inflammatory cytokines. STUDY DESIGN: GV was determined at 36 weeks post-menstrual age (PMA) in 768 infants 401-1000 g birth weight (BW). Association between blood cytokines measured through day of life 21 and GV was explored using linear regression models that adjusted for late-onset sepsis (LOS), BW, small-for-gestational age (SGA), gender, race, energy intake, and center. RESULTS: Serum interleukin-6 (IL-6) was increased at days 14 and 21 in LOS infants. LOS was associated with reduced energy intake and GV for weight (weight-GV) at 36 weeks PMA. Linear regression analysis controlling for LOS and energy intake showed significant relationships between increased IL-6 at days 14 and 21 with reduced weight-GV at 36 weeks PMA (p<0.0001). The relationship between day 21 IL-6 and weight-GV was not associated with LOS (p=0.12) when controlling for BW and energy intake. Both BW (p=0.02) and energy intake (p=0.003) influenced the relationship between day 14 IL-6 and weight-GV. CONCLUSIONS: IL-6 elevation during the first month of life is associated with lower weight-GV at 36 weeks PMA and may have a direct effect upon energy balance and postnatal growth.